Mild Cognitive Impairment (MCI) pada Aspek Kognitif dan Tingkat Kemandirian Lansia dengan Mini-Mental State Examination (MMSE) - Akhmad Akhmad; Sahmad Sahmad; Indriono Hadi; Lilin Rosyanti (Health Information : Jurnal Penelitian, 2019)
Aging reduces physical, psychological and social functioning. Cognitive impairment causes disabilities in daily functions and limits quality of life. In the elderly there is often a partial or total dependence on external assistance or care. The importance of a study to conduct a study on Mild Cognitive Impairment (MCI) on the Cognitive Aspects and the Level of Independence of the Elderly with a Mini-Mental State Examination (MMSE) measurement tool, in elderly people living in coastal areas who are part of the assisted blood of the nursing department. The type of research used is descriptive research, in August-December 2018 on the coast of Toronipa. The population in this study were all elderly who live in the Toronipa coastal area of ??Konawe Regency, an assessment instrument that functions to measure functional independence in self-care and mobility and is also used as a criterion in assessing functional ability for 10 minutes and assessing cognitive function in the areas of orientation, memory, attention and calculation, language construction and visuals. Patients score between 0 and 30 points, and cut-offs of 23/24 are usually used to indicate significant cognitive decline. Research result; Analysis on cognitive function: normal category 20 people (40.0%) while cognitive function disorders as many as 30 people (60.0%). The category of the independence level of the elderly, independent in carrying out daily activities as many as 48 people (96.0%), while those who experienced dependence amounted to 2 people (4.0%). The results of the analysis with the Chi Square test, the value of p = 0.510, meaning that the P value is greater than 0 , 05, so that there is no relationship between MCI from a cognitive aspect with the level of independence of the elderly in the coastal area of ??Toronipa.